2007
DOI: 10.1002/ca.20504
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical evaluation of the tibial nerve within the popliteal fossa

Abstract: The study has contributed to evaluate the tibial nerve and its vasculature anatomically. Ten preserved cadavers (5 male, 5 female) have been used for this study. Each cadaver was injected with red latex and through incisions the tibial nerve was exposed at the level of bifurcation of sciatic nerve. The tibial nerve in 85 % cadavers was located between middle and lower thirds at upper angle of popliteal fossa; whereas, in 15 % cadavers it was present below the piriformis muscle in gluteal region. The total leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Even the all-inside sutures have to be careful as well. 25-29 Snyder et al 5 reported the applications of hook all-inside mattress suture which was operated in the joint completely, without influences to the popliteal tendon and the popliteal hiatus, and injuring the common peroneal nerve. In this study, we also used the arthroscopic all-inside repair using a suture hook for the PFLM tears, and this suture technique has achieved good clinical effect in all 36 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Even the all-inside sutures have to be careful as well. 25-29 Snyder et al 5 reported the applications of hook all-inside mattress suture which was operated in the joint completely, without influences to the popliteal tendon and the popliteal hiatus, and injuring the common peroneal nerve. In this study, we also used the arthroscopic all-inside repair using a suture hook for the PFLM tears, and this suture technique has achieved good clinical effect in all 36 patients.…”
Section: Discussionmentioning
confidence: 99%
“…초음파를 통해 위중혈을 자침 시 자극하는 구조물들 의 심도는 피부두께 2.07±0.20 mm, 천근막 5.17±0.20 mm 이었다 4,16) . TN은 피부 표면으로부터 14.25±1.15 mm 깊이 에 존재하며 4,16,36) 이때 TN은 SM건과 BF건 사이 간격의 9.5% 에 해당하는 너비를 가지고 있다 31) . 일반적으로 PA는 TN보다 수 밀리미터 더 깊은 층에 존재하는데 피부로부터 측정한 결과 20.18±2.86 mm 떨어져 있다 4,16,17,36) .…”
Section: 해부학적 관점으로 이해한 위중 혈위unclassified
“…For blocking pain effectively, injections within the common connective tissue sheath have a higher success rate than injections outside the sheath (Lopez et al, 2014). Therefore, when considering nerve block, it is important for clinicians and researchers to understand the anatomical locations of the nerves (Driban et al, 2007).…”
Section: Introductionmentioning
confidence: 99%